What conditions are associated with household water vulnerability in the Arctic?. Issue 97 (July 2019) - Sohns, Antonia; Ford, James; Robinson, Brian E.; Adamowski, Jan
Highlights: Biophysical variability and socio-political changes contribute to household water vulnerability in the Arctic. Age dynamics and demographic shifts in Arctic regions are influencing household water vulnerability. Societal changes must be considered in present and future Arctic freshwater policy. Abstract: Increasing pressure on water resources from demographic shifts, climate change, and development patterns is affecting water access and water availability in Arctic households. There is an urgent need to improve understanding of the factors that contribute to Arctic household water vulnerability. This paper examines the key conditions or combinations of conditions associated with water access and water availability that collectively impact household water vulnerability in the Arctic based on an analysis of 28 case studies. Five conditions were identified through a literature review as contributing to household water vulnerability: inadequate freshwater policies, inadequate funding, inadequate infrastructure, biophysical variability, and societal changes. We used qualitative comparative analysis (QCA) to explore the configurations of these conditions along causal pathways that lead to household water vulnerability. The case studies were grouped into one of three typologies of household water vulnerability: political ecology, water security, or socio-hydrology. Through the analysis, absence of societal change in the Arctic was found to be a necessary condition for the political ecology typology, and the presence of freshwater policies and societal change in the Arctic were observed to be necessary conditions for the socio-hydrology typology. The research reveals how societal changes and anthropogenic factors contribute to household water vulnerability and must be considered in present and future Arctic freshwater policy.